Memoria de trabajo en relación con el trastorno de conducta y callo emocional - Amador Zavala, Laura Olivia (Archivos de criminología, seguridad privada y criminalística, 2021)
The findings regarding the functioning of working memory (WM) in youngs with Conduct Disorder (CD) are not conclusive. Therefore, the main purpose was to compare possible differences in WM depending on the presence of CD and Callous-Unemotional traits (CU). Method: 101 adolescents (15-18 years old), of both sexes, participated. Two groups were formed, with CD symptoms (32.6%) and one control (67.4%), subsequently, another 2 according to the level of CU (high/low). Direct and inverse digits test was applied to all of them. Results: No differences were observed between the groups with CD and without CD. Regarding the CU, there were only differences in the Inexpressivity dimension where the group with highs traits obtained greater performance in direct digits. Conclusion: the findings show that there are no WM deficits associated with CD or CU.